Pyrolysed 3D‐Carbon Scaffolds Induce Spontaneous Differentiation of Human Neural Stem Cells and Facilitate Real‐Time Dopamine Detection. (11th September 2014) - Amato, Letizia; Heiskanen, Arto; Caviglia, Claudia; Shah, Fozia; Zór, Kinga; Skolimowski, Maciej; Madou, Marc; Gammelgaard, Lauge; Hansen, Rasmus; Seiz, Emma G.; Ramos, Milagros; Moreno, Tania Ramos; et al.
<x xml:space="preserve">Abstract</x> Structurally patterned pyrolysed three‐dimensional carbon scaffolds (p3D‐carbon) are fabricated and applied for differentiation of human neural stem cells (hNSCs) developed for cell replacement therapy and sensing of released dopamine. In the absence of differentiation factors (DF) the pyrolysed carbon material induces spontaneous hNSC differentiation into mature dopamine‐producing neurons and the 3D‐topography promotes neurite elongation. In the presence and absence of DF, ≈73–82% of the hNSCs obtain dopaminergic properties on pyrolysed carbon, a to‐date unseen efficiency in both two‐dimensional (2D) and 3D environment. Due to conductive properties and 3D environment, the p3D‐carbon serves as a neurotransmitter trap, enabling electrochemical detection of a significantly larger dopamine fraction released by the hNSC derived neurons than on conventional 2D electrodes. This is the first study of its kind, presenting new conductive 3D scaffolds that provide highly efficient hNSC differentiation to dopaminergic phenotype combined with real‐time in situ confirmation of the fate of the hNSC‐derived neurons.